2018
DOI: 10.1128/mbio.01603-18
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Studies of Chlorobiaceae Suggest that Bacillithiol Derivatives Are the Most Widespread Thiols in Bacteria

Abstract: Low-molecular-weight thiols are key metabolites that participate in many basic cellular processes: central metabolism, detoxification, and oxidative stress resistance. Here we describe a new thiol, N-methyl-bacillithiol, found in an anaerobic phototrophic bacterium and identify a gene that is responsible for its synthesis from bacillithiol, the main thiol metabolite in many Gram-positive bacteria. We show that the presence or absence of this gene in a sequenced genome accurately predicts thiol content in dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Now, Hiras and colleagues report the identification and characterization of a novel thiol from the green sulfur bacterium Chlorobium tepidum (15). Like Chromatium sp., Chlorobia perform anoxygenic photosynthesis, oxidizing reduced sulfur compounds for CO 2 fixation and are obligate anaerobes.…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…Now, Hiras and colleagues report the identification and characterization of a novel thiol from the green sulfur bacterium Chlorobium tepidum (15). Like Chromatium sp., Chlorobia perform anoxygenic photosynthesis, oxidizing reduced sulfur compounds for CO 2 fixation and are obligate anaerobes.…”
Section: Commentarymentioning
confidence: 99%
“…Chlorobia and Chloroflexus dominate the H 2 S-containing geothermal environments found in areas such as Mammoth hot springs in Yellowstone National Park. Hiras et al (15) report that C. tepidum, Chlorobium phaeobacterioides, and Prosthecochloris sp.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study identified a BSH derivative with an N-methylated cysteine as N-methyl-BSH in anaerobic phototrophic Chlorobiaceae, suggesting that BSH derivatives are more widely distributed and not restricted to Gram-positive firmicutes (Hiras et al, 2018). In S. aureus and Bacillus subtilis, BSH was characterized as cofactor of thiol-S-transferases (e.g.…”
Section: Introductionmentioning
confidence: 99%